HAK REPRODUKSI PEREMPUAN dalam Perspektif Syariat Islam - Angga, La Ode (MUWAZAH, 2011)
Islam as Din has more authority to function to save and liberate people from tyranny-the tyranny of other human beings. The Qur’an mentions this function as “yukhrijuhum min al zhulumat ila Al-Nur” (removing people from darkness to light). View of human equality, men and women in the Qur’an include aspects of spirituality, intellect and sexuality as well as all other practical life activities. About the relationship of sexuality, the Qur’an states: “and they (women) have rights comparable to their obligations”. Ibn Abbas, a prominent companion of the Prophet, commenting on this verse by saying: “I like dressing up for my wife as I like her dress up for me”. Another verse also says: “they (women) are a garment for you and you are garments for them”.